(untitled) (ACME, 2022)
By focusing on the challenging translation of the so-called basilicus iactus mentioned in Plautus’ play Curculio, this article attempts to provide a new contribution to the study of Latin play culture. On the basis of evidence from within the text, in particular regarding the dramatic identity of its protagonists and the narrative isotopies present, and thanks to evidence from outside the play, specifically from some ancient Greek cultic traditions, this research proposes to understand the expression basilicus iactus not as “king’s throw” but as “queen’s throw”, with an implicit reference to the goddess Venus implied by the knucklebones throw that took its name from the deity.